A Patient With Pansynostosis and Williams-Beuren Syndrome. Issue 1 (January 2016) - Kansy, Katinka; Freudlsperger, Christian; Hoffmann, Jürgen; Engel, Michael
Abstract : Background: Williams-Beuren syndrome (WBS) is a multisystemic genetic disorder caused by a gene deletion at gene locus 7q11.23. This article presents the first described case of a patient with WBS and simultaneous pansynostosis. Case Presentation: This article presents the management of this young Caucasian boy from birth until the age of 12 years and provides an overview of previously described manifestations of WBS in the craniofacial region. Conclusions: This case demonstrates the surgical treatment of pansynostosis in a child with WBS and might provide interesting aspects in the diagnostics and management of this rare malformation.